The female scientist in natural science textbooks: A look through bachelardian epistemological lenses (Revista Contexto & Educação, 2026)
The female scientist figure has contributed and continues to contribute significantly to the development of Science and Technology (ST), yet they remain invisible in many educational tools, including Textbooks, which persist in reproducing stereotypes, especially regarding ST students. From this perspective, we aimed to verify whether the epistemological obstacle of unitary and pragmatic knowledge was present in the way images of scientists are presented in High School Natural Sciences and Technology. To this end, we aimed to corpus the seven collections approved by the 2021 National Book and Teaching Material Program were analyzed using Discursive Textual Analysis as the analytical methodology, divided into three stages: unitarization, categorization, and communication. This investigation yielded two categories: i) Alone or accompanied? Focusing on a ST from the last century, white, gray, and in laboratories; and ii) Weaving together future possibilities and challenges: the female figure in modernity. The lack of female representation in ST may allude to an obstacle to unitary and pragmatic knowledge due to the fact that it generalizes science as masculine and/or performed by an elderly, white person with gray hair and beard, in a laboratory next to their glassware, thus neglecting and rendering other groups invisible. That said, the textbooks continue to reproduce a certain standard of scientist or even suggest that this is not practiced in modernity, due to the lack of examples presented. Therefore, these representations require careful consideration so that we do not continue to block any insertions in the scientific-technological environment.
Keywords: feminine; science-technology; generalization; stereotypes